Pengaruh Kepemimpinan Transformasional Dan Pemberian Kompensasi Terhadap Prestasi Kerja PegawaiBadan Pengelolaan Keuangan Dan Pendapatan Daerah (BPKPD) Kabupaten Pamekasan Yang Dimediasi Oleh Organizational Citizenship Behaviour (OCB) - Woro Utari; Eddy Suryanto; Nugroho Mardi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Eddy Suryanto, 2024. The Influence of Transformational Leadership and Providing Compensation on Employee Work Performance by the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) Mediated by Organizational Citizenship Behavior (OCB). Wijaya Putra University Postgraduate Program Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 50 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To determine the description of transformational leadership, compensation, Organizational Citizenship Behavior (OCB) and work performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD). 2) To test and analyze whether transformational leadership has an influence on work performance. 3) To test and analyze whether transformational leadership has an influence on Organizational Citizenship Behavior (OCB). 4) To test and analyze whether giving rewards has an influence on the work performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD). 5) To test and analyze whether giving rewards has an influence on Organizational Citizenship Behavior (OCB). 6) To test and analyze whether Organizational Citizenship Behavior (OCB) has an influence on employee work performance. 7) To test and analyze whether transformational leadership has an indirect influence on work performance which is mediated by Organizational Citizenship Behavior (OCB). 8) To test and analyze whether giving rewards has an indirect influence on work performance which is mediated by Organizational Citizenship Behavior (OCB). The research results show that: 1) transformational leadership has no direct positive and insignificant effect on work performance as evidenced by the original sample value of 0.136 and p-values ​​of 0.140. 2) Transformational leadership has a direct and significant positive effect on Organizational Citizenship Behavior (OCB), proven by the original sample value of 0.282 and p-values ​​of 0.004. 3) Providing compensation has a direct positive and significant effect on work performance as evidenced by the original sample value of 0.498 and p-values ​​of 0.000. 4) Providing compensation has a direct and significant positive effect on Organizational Citizenship Behavior (OCB), proven by the original sample value of 0.651 and p-values ​​of 0.000. 5) Organizational Citizenship Behavior (OCB) has a direct and significant positive effect on work performance as evidenced by the original sample value of 0.338 and p-values ​​of 0.022. 6) Transformational leadership has a significant positive indirect effect on work performance and Organizational Citizenship Behavior (OCB), proven by the original sample value of 0.095 and p-values ​​of 0.135. 7) Providing compensation has a significant positive indirect effect on work performance and Organizational Citizenship Behavior (OCB) with a path coefficient value of 0.220 and a p-value of 0.026.